2013
DOI: 10.1093/mnras/stt2048
|View full text |Cite
|
Sign up to set email alerts
|

Structure of advection-dominated accretion discs with outflows: the role of toroidal magnetic fields

Abstract: The main aim of this paper is studying the effect of toroidal magnetic field on the structure of Advection-Dominated Accretion Flows (ADAF) in the presence of the turbulence viscosity and diffusivity due to viscosity and magnetic field respectively. We use self-similar assumption in radial direction to solve the magnetohydrodynamic (MHD) equations for hot accretion disk. We use spherical coordinate (r, θ, ϕ) to solve our equation. The toroidal component of magnetic field is considered and all three components … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
4
15
0
Order By: Relevance
“…In our previous work, Samadi et al 2014, we investigated the thickness of a hot accretion flow in the presence of the toroidal magnetic field and showed that the disc thickness decreases with increasing the magnetic field strength, and the vertical aspect of the disc is significantly changed in comparison with a nonmagnetic case. Mosallanezhad, Abbassi & Beiranvand (2014), (hereafter MAB14) followed JW11 by adding the toroidal magnetic field. Their results showed that the existence of a magnetic field and its resistivity in a disc can produce more advective energy.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, Samadi et al 2014, we investigated the thickness of a hot accretion flow in the presence of the toroidal magnetic field and showed that the disc thickness decreases with increasing the magnetic field strength, and the vertical aspect of the disc is significantly changed in comparison with a nonmagnetic case. Mosallanezhad, Abbassi & Beiranvand (2014), (hereafter MAB14) followed JW11 by adding the toroidal magnetic field. Their results showed that the existence of a magnetic field and its resistivity in a disc can produce more advective energy.…”
Section: Introductionmentioning
confidence: 99%
“…In the one-dimensional works, the existence of wind is often an assumption (e.g. Blandford & Begelman 1999;Akizuki & Fukue 2006;Abbassi et al 2008;Zhang & Dai 2008;Bu et al 2009 Mosallanezhad et al 2014;Gu 2015;Samadi & Abbassi 2016 ) but not all (e.g., Narayan & Yi 1995 and references therein). In all these works magnetic field is not included.…”
Section: Introductionmentioning
confidence: 99%
“…There are several analytical investigations based on the self-similar assumption that probe the magnetic field effects in hot accretion flows (Akizuki & Fukue 2006;Abbassi et al 2008;Zhang & Dai 2008;Bu et al 2009;Mosallanezhad et al 2014;Samadi et al 2017;Bu & Mosallanezhad 2018;Deng & Bu 2019). In practice, the analytical studies are powerful tools to understand the physical properties of inflow and wind from accretion flow.…”
Section: Introductionmentioning
confidence: 99%